Metal ceramic composite material for preparing hydrogen-rich water as well as preparation and application of metal ceramic composite material
By preparing porous metal-ceramic composite materials and utilizing a combination of magnesium-based alloys, aluminum-based alloys, ceramic matrices, and functional additives, the problems of low hydrogen production efficiency, short lifespan, and uncontrollable reaction in existing porous metal-ceramic composite materials have been solved, achieving efficient and controllable hydrogen release and long-term use.
Patent Information
- Application Number
- CN202511034307.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-25
- Publication Date
- 2025-12-19
AI Technical Summary
Existing porous metal-ceramic composite materials have problems such as limited hydrogen production efficiency, short service life, poor reaction controllability, and easy powder shedding from the material surface when preparing hydrogen-rich water.
A porous metal-ceramic composite material was prepared by combining core-shell structured magnesium-based alloy particles, doped aluminum-based alloy particles, a ceramic matrix, functional additives, and sintering aids through mixing, molding, and sintering. The Mg-Ni alloy provides efficient hydrogen production active sites, the ZnO coating layer enables pH-responsive hydrogen production rate regulation, the Al-Ga-In alloy disrupts the passivation layer, Pt nanoclusters catalyze water splitting, and hydrophilic graphene quantum dots improve hydrogen dissolution efficiency.
It achieves efficient and controllable hydrogen release, extends the service life of materials, increases the hydrogen production rate, enhances the hydrophilicity of materials, inhibits the agglomeration of metal particles, improves the density of materials, and achieves a service life of 6 to 12 months.
Smart Images

Figure SMS_1
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical fields of cermet materials and water treatment, and particularly relates to a cermet composite material for preparing hydrogen-rich water and preparation and application thereof. BACKGROUND
[0002] Hydrogen-rich water is water rich in hydrogen. By adding hydrogen to ordinary drinking water, it becomes a carrier of hydrogen. The hydrogen dissolved in water does not change the physical properties of water, so it does not affect the function of water. Hydrogen-rich water not only has the function of ordinary drinking water, but also can effectively remove free radicals in the body, prevent and treat various symptoms caused by free radicals, promote metabolism, and play a role in health care. In addition, hydrogen-rich water not only has great benefits for human health, but also has many benefits for the innovative development of agriculture and aquaculture, for example: hydrogen-rich water can improve the stress resistance of crops and resist plant stress; promote plant growth and development; be beneficial to the preservation of fruits and vegetables; replace pesticides for disease prevention and killing of crops; hydrogen-rich water can improve water quality, increase the dissolved oxygen content of water, and promote the metabolism, growth and reproduction of aquatic organisms, etc.
[0003] Porous cermet composite material is an advanced functional material combining the properties of metal and ceramic. It can realize hydrogen production by combining nano magnesium powder with ceramic matrix, and has unique advantages in the field of hydrogen-rich water preparation. However, the existing porous cermet composite material has the following disadvantages when used to prepare hydrogen-rich water: nano magnesium powder is easy to be oxidized to form a passivation layer, which hinders the continuous reaction and limits the hydrogen production efficiency; the material fails after the consumption of the metal phase, and generally needs to be replaced after 1-3 months, with a short service life; the reaction controllability is poor, and the hydrogen generation rate is difficult to adjust according to demand; the material surface is easy to fall off powder, affecting the use experience, etc. SUMMARY
[0004] The present application provides a cermet composite material for preparing hydrogen-rich water and preparation and application thereof, which solves the technical problems of limited hydrogen production efficiency, short service life, poor reaction controllability, and easy powder falling off from the material surface of traditional materials through material composition innovation.
[0005] The cermet composite material for preparing hydrogen-rich water provided by the present application has a porous structure and is prepared by sintering after mixing and molding of raw materials; The raw materials include nano metal phase, doped aluminum-based alloy particles, ceramic matrix, functional additives, pore-forming agents and sintering aids in a weight ratio of 10-30:10-30:30-60:5-15:5-10:2-5; The nano metal phase is magnesium-based alloy particles with a core-shell structure, which includes an inner core and an outer shell. The inner core is a magnesium-nickel (Mg-Ni) alloy, and the outer shell is a zinc oxide (ZnO) coating layer. The doped aluminum-based alloy particles are aluminum-gallium-indium (Al-Ga-In) alloy particles with a surface loaded with platinum (Pt) nanoclusters. The functional adjuvant is hydrophilic graphene quantum dots.
[0006] In some embodiments of the present application, the thickness of the zinc oxide coating layer in the magnesium-based alloy particles with core-shell structure is 5 nm to 20 nm.
[0007] In some embodiments of the present application, the loading amount of platinum in the doped aluminum-based alloy particles is 0.1wt% to 1wt%.
[0008] In some embodiments of the present application, the ceramic matrix comprises nanometer aluminum oxide (Al2O3), nanometer titanium dioxide (TiO2), zirconium dioxide (ZrO2) and magnesium oxide (MgO); preferably, the ceramic matrix comprises nanometer aluminum oxide, nanometer titanium dioxide, zirconium dioxide and magnesium oxide in a molar ratio of 1-4:1:1-3:1.
[0009] In some embodiments of the present application, the pore-forming agent comprises ammonium bicarbonate (NH4HCO3) and polymethyl methacrylate (PMMA); preferably, the pore-forming agent comprises ammonium bicarbonate and polymethyl methacrylate in a weight ratio of 1-4:1.
[0010] In some embodiments of the present application, the pore-forming agent is composed of a mixture of ammonium bicarbonate and polymethyl methacrylate (PMMA) microspheres.
[0011] In an embodiment of the present application, the sintering adjuvant is cerium borate (CeBO3).
[0012] In an embodiment of the present application, the hydrophilic graphene quantum dots are carboxyl-modified graphene quantum dots.
[0013] In some embodiments of the present application, the specific surface area of the metal-ceramic composite material for hydrogen-rich water production is 50 m² / g to 100 m² / g.
[0014] The present application also provides a preparation method of the metal-ceramic composite material for hydrogen-rich water production as described above, comprising the following steps: mixing and forming nanometer metal phase, doped aluminum-based alloy particles, ceramic matrix, functional adjuvant, pore-forming agent and sintering adjuvant, sintering, to obtain the metal-ceramic composite material for hydrogen-rich water production.
[0015] In some embodiments of the present application, the mixing and forming method is dry pressing or injection molding, and the dry pressing pressure is 50 MPa to 100 MPa.
[0016] In some embodiments of the present application, the sintering process comprises: heating to 600-800°C in a protective atmosphere for 2-4 hours, then holding at 400-500°C in a hydrogen atmosphere for 1-2 hours to form a porous structure, and finally cooling to room temperature to obtain the metal ceramic composite material for preparing hydrogen-rich water.
[0017] The present application also provides the use of the metal ceramic composite material for preparing hydrogen-rich water as described above and / or prepared according to the method as described above in the preparation of hydrogen-rich water.
[0018] The present application also provides a device for preparing hydrogen-rich water, comprising a hydrogen-rich water preparation module containing the metal ceramic composite material for preparing hydrogen-rich water as described above and / or prepared according to the method as described above.
[0019] The present application has the following beneficial effects: The metal ceramic composite material for preparing hydrogen-rich water of the present application realizes efficient and controllable hydrogen release through the synergy of multiple metals and multiple components, and prolongs the service life of the material. Among them, the Mg-Ni alloy provides efficient hydrogen production active sites, and the Ni element in it can inhibit the oxidation of magnesium and promote electron transfer; the ZnO coating layer can slowly dissolve under weak acidic conditions to realize pH-responsive hydrogen production rate regulation; the Al-Ga-In alloy can continuously destroy the passivation layer through the micro-battery effect, prolonging the service life of the material; the Pt nanocluster can catalyze water decomposition, significantly improving the hydrogen production rate; the addition of hydrophilic graphene quantum dots can enhance the hydrophilicity of the material, promote the dissolution efficiency of hydrogen in water, and increase the saturated hydrogen concentration of hydrogen-rich water.
[0020] The metal ceramic composite material for preparing hydrogen-rich water of the present application has a porous structure and a high specific surface area, which can effectively inhibit metal particle agglomeration and prolong the service life of the material.
[0021] The metal ceramic composite material for preparing hydrogen-rich water of the present application is prepared by adding a sintering aid CeBO3, which interacts with the ceramic matrix, improves the viscosity of the liquid phase, promotes sintering densification, and thus improves the density of the material.
[0022] In summary, the metal ceramic composite material for preparing hydrogen-rich water of the present application has the characteristics of high catalytic activity, long-acting controllable hydrogen release, and firm surface bonding, and the service life can reach 6-12 months, which has good application value in the preparation of hydrogen-rich water. DETAILED DESCRIPTION
[0023] The present application is described in greater detail by the following specific examples, and other advantages and effects of the present application can be easily understood by persons skilled in the art from the disclosure of this specification. The present application can also be implemented or applied by other different specific embodiments, and various modifications or changes can be made to the details in this specification based on different views and applications without departing from the spirit of the present application, and the following examples and features in the examples can be combined with each other without conflict.
[0024] In the present application, the term "plurality" means two or more, unless otherwise specified.
[0025] The character " / " represents an "or" relationship between the objects before and after it. For example, A / B means A or B.
[0026] The term "and / or" is a description of the relationship between the objects, which means that there can be three relationships. For example, A and / or B means that there are three relationships of A or B, or A and B.
[0027] An embodiment of the present application provides a metal ceramic composite material for preparing hydrogen-rich water, which has a porous structure and is prepared by sintering a raw material after mixing and molding; The raw material includes a nano-metal phase, a doped aluminum-based alloy particle, a ceramic matrix, a functional aid, a pore-forming agent, and a sintering aid, with a weight ratio of 10-30:10-30:30-60:5-15:5-10:2-5. The nano-metal phase is a magnesium-based alloy particle with a core-shell structure, which includes an inner core and an outer shell. The inner core is a Mg-Ni alloy, and the outer shell is a ZnO coating layer. The doped aluminum-based alloy particle is an Al-Ga-In alloy with Pt nanoclusters loaded on the surface. The functional aid is a hydrophilic graphene quantum dot.
[0028] The metal ceramic composite material for preparing hydrogen-rich water has the following characteristics and advantages: 1. Multi-metal synergistic hydrogen release mechanism: Mg-Ni alloy provides efficient hydrogen production active sites, while Ni element inhibits magnesium oxidation and promotes electron transfer; Al-Ga-In alloy continuously destroys the passivation layer through micro-battery effect, prolonging the service life of the material; Pt nanoclusters catalyze water decomposition, significantly improving the hydrogen production rate; hydrophilic graphene quantum dots enhance the hydrophilicity of the material, promote the dissolution efficiency of hydrogen in water, and increase the saturation hydrogen concentration of hydrogen-rich water.
[0029] 2. Controllable hydrogen release structure design: ZnO coating layer slowly dissolves under weak acidic conditions, realizing pH-responsive hydrogen production rate regulation.
[0030] 3. The porous structure provides high specific surface area while inhibiting metal particle agglomeration, prolonging the service life of the material.
[0031] In some embodiments of the present application, the magnesium-based alloy particles with core-shell structure are prepared by depositing zinc oxide on the surface of Mg-Ni alloy powder through deposition reaction of zinc source under the action of precipitant. The zinc source acts as a precursor in the deposition reaction, including but not limited to zinc acetate, zinc chloride, zinc nitrate, zinc sulfate, and / or zinc oxalate, etc. The precipitant includes but is not limited to sodium hydroxide, potassium hydroxide, and / or ammonia, etc. The deposition reaction temperature is, for example, 60-80°C. The pH of the deposition reaction system is, for example, controlled at 8-10. The concentration of the zinc source in the deposition reaction system is, for example, 0.05-0.2 mol / L. The deposition reaction time is, for example, 2-4 hours, referring to the reaction time after the zinc source is added completely. The thickness of the ZnO coating layer in the magnesium-based alloy particles with core-shell structure is preferably 5-20 nm, which can be controlled by adjusting the concentration of the zinc source and the deposition reaction time.
[0032] For example, the preparation method of the magnesium-based alloy particles with core-shell structure includes the following steps: A1. Alloy powder pretreatment: after surface activation of the Mg-Ni alloy powder, the Mg-Ni alloy powder is dispersed in a solvent to prepare a Mg-Ni alloy powder suspension; A2. Preparation of precursor solution: the zinc source is added to the solvent to prepare a zinc source solution, and the precipitant is added to the solvent to prepare a precipitant solution; A3. Deposition reaction: the Mg-Ni alloy powder suspension is heated to 60-80°C, and the precipitant solution is added dropwise under stirring until the pH of the system is stabilized at 8-10. Then the zinc source solution is added dropwise, and after the addition is completed, the stirring reaction is continued for 2-4 hours to make ZnO uniformly deposited on the surface of the Mg-Ni alloy powder. The chemical reaction equation is as follows: Zn 2+ + 2OH−== Zn(OH)2↓ Zn(OH)2== ZnO + H2O A4. Post-treatment: after the deposition reaction is completed, the obtained reaction liquid is centrifuged to collect the precipitate, which is washed to remove impurities, and then dried to obtain the ZnO-coated Mg-Ni alloy powder, i.e., the magnesium-based alloy particles with core-shell structure.
[0033] In step A1, the surface activation of the Mg-Ni alloy powder refers to the removal of the oxide layer on the surface of the Mg-Ni alloy powder. The operation method is, for example, placing the Mg-Ni alloy powder in a dilute hydrochloric acid solution, and ultrasonic cleaning at room temperature to remove the surface oxide layer. The concentration of the dilute hydrochloric acid solution is, for example, 1-3 wt%, and the ultrasonic cleaning time is, for example, 5-10 minutes.
[0034] In steps A1, A2 and A3, the solvent includes but is not limited to ethanol and / or water, and the suspension and solution preparation method includes but is not limited to stirring, ultrasonic dispersion, etc.
[0035] In step A3, the stirring rate is, for example, 300 rpm-500 rpm; the deposition reaction process can be protected by passing inert gas (such as nitrogen) to prevent alloy oxidation.
[0036] In step A4, when centrifuging, the centrifuge speed is, for example, 3000 rpm-5000 rpm, and the centrifuging time is, for example, 8-20 minutes; the impurity removal method includes but is not limited to water washing and / or ethanol washing, etc., preferably water washing first and then ethanol washing, the number of water washing is recommended to be at least 3 times, and the number of ethanol washing is recommended to be at least 2 times; the drying method is preferably vacuum drying, the drying temperature is preferably 50°C-70°C, and the drying time is not less than 8 hours.
[0037] In some embodiments of the present application, the doped aluminum-based alloy particles are prepared by reducing Pt ions to Pt and loading Pt on the surface of Al-Ga-In alloy powder through a reduction reaction of a platinum source under the action of a reducing agent, and the loading amount of platinum in the doped aluminum-based alloy particles is preferably 0.1wt%-1wt%. The platinum source includes but is not limited to chloroplatinic acid, potassium tetrachloroplatinate and / or sodium hexachloroplatinate, etc., the reducing agent includes but is not limited to sodium borohydride (NaBH4), hydrazine hydrate, etc., the reduction reaction temperature is, for example, room temperature, the pH of the reduction reaction system is controlled at, for example, 10-12, the concentration of the platinum source in the reduction reaction system is, for example, 0.01mol / L-0.05mol / L, the specific concentration is calculated according to the Pt loading amount, and the reduction reaction time is, for example, 0.5-2 hours, which refers to the reaction time after the platinum source is added.
[0038] For example, the preparation method of the doped aluminum-based alloy particles includes the following steps: B1, solution preparation: adding a platinum source into a solvent to prepare a platinum source solution; B2, reduction reaction to load Pt: uniformly dispersing Al-Ga-In alloy powder in the platinum source solution, then adding a reducing agent dropwise to reduce Pt 2+ to Pt, adjusting the pH after the dropwise addition is completed, and continuing to stir the reaction; after the reduction reaction is completed, the obtained reaction solution is filtered, washed to neutral, and dried to obtain Al-Ga-In alloy loaded with Pt nanoclusters, i.e., the doped aluminum-based alloy particles.
[0039] In step B1, the solvent includes but is not limited to ethanol and / or water, etc.
[0040] In step B2, the Al-Ga-In alloy powder is uniformly dispersed in the platinum source solution by stirring, for example, for 2-4 hours; the washing method is, for example, water washing; and the drying method is preferably vacuum drying, preferably at a temperature of 50-70°C, for a period of no less than 8 hours.
[0041] In some embodiments of the present application, the ceramic matrix comprises nano-Al2O3, nano-TiO2, ZrO2 and MgO, and the molar ratio of nano-Al2O3, nano-TiO2, ZrO2 and MgO is 1-4:1:1-3:1, preferably 3:2:2:1.
[0042] In some embodiments of the present application, the pore-forming agent comprises NH4HCO3 and PMMA, and the weight ratio of NH4HCO3 to PMMA is 1-4:1, preferably 2:1. Preferably, the pore-forming agent is composed of a mixture of NH4HCO3 and PMMA microspheres, with a particle size range of 50-200 μm. PMMA microspheres are tiny spherical bodies composed of polymethyl methacrylate, usually appearing as white powder particles, like delicate snowflakes.
[0043] In an embodiment of the present application, the sintering aid is cerium borate (CeBO3). The addition of CeBO3 as a sintering aid can interact with the ceramic matrix, improve the viscosity of the liquid phase, promote sintering densification, and thus improve the density of the composite material.
[0044] In an embodiment of the present application, the hydrophilic graphene quantum dots are carboxyl-modified graphene quantum dots with an average particle size of preferably 5-10 nm. Of course, hydrophilic graphene quantum dots obtained by other modification methods can also be used.
[0045] In some embodiments of the present application, the specific surface area of the metal ceramic composite material for preparing hydrogen-rich water is 50-100 m² / g.
[0046] Another embodiment of the present application provides a preparation method of the metal ceramic composite material for preparing hydrogen-rich water as described above, comprising the following steps: mixing and forming a nano-metal phase, doped aluminum-based alloy particles, a ceramic matrix, a functional aid, a pore-forming agent and a sintering aid, and sintering to obtain the metal ceramic composite material for preparing hydrogen-rich water.
[0047] In some embodiments of the present application, the mixing and forming method is dry pressing or injection molding, and the dry pressing pressure is 50-100 MPa.
[0048] In some embodiments of the present application, the sintering process comprises: heating to 600-800°C in a protective atmosphere (such as nitrogen, argon, etc.) for 2-4 hours, then heating to 400-500°C in a hydrogen atmosphere for 1-2 hours to form a porous structure, and finally cooling to room temperature to obtain the metal ceramic composite material for hydrogen-rich water production.
[0049] Another embodiment of the present application provides the use of the metal ceramic composite material for hydrogen-rich water production as described above and / or prepared according to the method as described above in the preparation of hydrogen-rich water, the application fields of which include but are not limited to drinking water treatment, agriculture and aquaculture, medical care, etc., and there are many specific application methods, such as: making ordinary drinking water into hydrogen-rich water, activating agricultural irrigation water, increasing hydrogen in aquaculture water, using it for hydrogen-rich water therapy, using it for the preparation of functional skin care products, etc.
[0050] Another embodiment of the present application provides a device for producing hydrogen-rich water, which comprises a hydrogen-rich water production module containing the metal ceramic composite material for hydrogen-rich water production as described above and / or prepared according to the method as described above. The device is, for example, a household water purifier, a hydrogen-rich water cup, an irrigation water activation device, an aquaculture water hydrogen-increasing equipment, a hydrogen-rich water therapy equipment, etc., and the metal ceramic composite material for hydrogen-rich water production can be made into a hydrogen-rich water ceramic sheet, which is installed in the above-mentioned device to increase hydrogen, produce hydrogen and prepare hydrogen-rich water.
[0051] The following specific examples are used to illustrate the present application in detail. It should also be understood that the following examples are only used to illustrate the present application, and cannot be understood as limiting the scope of protection of the present application. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present application are within the scope of protection of the present application. The following examples of specific process parameters, etc. are only one example in the appropriate range, i.e. those skilled in the art can select within the appropriate range according to the description herein, and are not limited to the specific values of the following examples.
[0052] Example 1 This example provides a magnesium-based alloy particle with core-shell structure (referred to as Mg-Ni / ZnO powder), and the preparation method steps are as follows: 1. Alloy powder pretreatment Surface activation: put the Mg-Ni alloy powder into 1wt% dilute hydrochloric acid solution, ultrasonic cleaning at room temperature for 10 minutes to remove the surface oxide layer; repeatedly rinse with deionized water until neutral, then wash with anhydrous ethanol for 2 times, and vacuum dry at 60°C for 2 hours.
[0053] Dispersion treatment: The surface-activated Mg-Ni alloy powder was dispersed in anhydrous ethanol, ultrasonically dispersed for 30 minutes to form a uniform suspension.
[0054] 2. Preparation of precursor solution Preparation of zinc source solution: zinc acetate dihydrate (Zn(CH3COO)2·2H2O) was weighed and prepared into a 0.1 mol / L ethanol solution, and magnetically stirred for 30 minutes until completely dissolved.
[0055] Preparation of precipitant solution: NaOH was weighed and prepared into a 0.2 mol / L ethanol solution, and deionized water was slowly added (water to ethanol volume ratio of 1:10).
[0056] 3. Deposition reaction Temperature control: the Mg-Ni alloy powder suspension was placed in a constant temperature water bath, heated to 70°C, and mechanically stirred at a stirring rate of 400 rpm.
[0057] pH adjustment: NaOH solution was slowly added until the pH value of the suspension was stable at 8-10, and stirring was continued during the process.
[0058] Deposition reaction: the zinc source solution was added at a rate of 1 mL / min, and nitrogen was introduced to protect the alloy from oxidation. After the addition was completed, stirring was continued for 3 hours to allow uniform deposition of ZnO.
[0059] 4. Post-treatment and characterization Washing and drying: centrifugal separation (4000 rpm, 10 minutes), collection of the precipitate; washing with deionized water (3 times) and anhydrous ethanol (2 times) to remove impurities; vacuum drying at 60°C for 12 hours to obtain ZnO-coated Mg-Ni alloy powder, with a ZnO coating layer thickness of 10 nm.
[0060] Example 2 This example provides a doped aluminum-based alloy particle (referred to as Al-Ga-In / Pt powder), and the preparation method steps are as follows: 1. Preparation of impregnation solution: a 0.02 mol / L chloroplatinic acid (H2PtCl6) ethanol solution was prepared, and the amount was calculated according to the Pt loading amount (0.1-1 wt%); 2. Loading process: Al-Ga-In alloy powder was dispersed in H2PtCl6 ethanol solution, stirred at room temperature for 3 hours; 0.1 mol / L NaBH4 solution was slowly added to reduce Pt 2+ , control pH=10-12; continue stirring for 1 hour, then filter, wash with deionized water to neutral, vacuum drying at 60°C for 12 hours to obtain Al-Ga-In alloy powder loaded with Pt nanoclusters on the surface.
[0061] Example 3 The embodiment provides a metal ceramic composite material for preparing hydrogen-rich water, and a preparation process thereof is as follows. S1, the nano metal phase, the doped aluminum-based alloy particles, the ceramic matrix, the functional additive, the pore-forming agent and the sintering aid are taken in a weight ratio of 10:10:30:5:5:2, mixed and dry-pressed into a shape under 80 MPa; wherein the nano metal phase is the Mg-Ni / ZnO powder in the embodiment 1, the doped aluminum-based alloy particles are the Al-Ga-In / Pt powder in the embodiment 2; the ceramic matrix is composed of nano Al2O3, nano TiO2, ZrO2 and MgO in a molar ratio of 3:2:2:1; the functional additive is a surface carboxyl-modified graphene quantum dot with an average particle size of 8 nm; the pore-forming agent is composed of NH4HCO3 and PMMA microspheres in a weight ratio of 2:1, and the particle size ranges from 50 μm to 200 μm; and the sintering aid is CeBO3.
[0062] S2, the temperature is raised to 600 DEG C in an argon atmosphere and kept for 4 hours, then kept for 2 hours at 400 DEG C in a hydrogen atmosphere, a porous structure is formed, and finally the temperature is lowered to room temperature, to obtain the metal ceramic composite material for preparing hydrogen-rich water.
[0063] Example 4 The embodiment provides a metal ceramic composite material for preparing hydrogen-rich water, and a preparation process thereof is as follows. S1, the nano metal phase, the doped aluminum-based alloy particles, the ceramic matrix, the functional additive, the pore-forming agent and the sintering aid are taken in a weight ratio of 20:20:50:10:8:3, mixed and dry-pressed into a shape under 80 MPa; wherein the nano metal phase is the Mg-Ni / ZnO powder in the embodiment 1, the doped aluminum-based alloy particles are the Al-Ga-In / Pt powder in the embodiment 2; the ceramic matrix is composed of nano Al2O3, nano TiO2, ZrO2 and MgO in a molar ratio of 3:2:2:1; the functional additive is a surface carboxyl-modified graphene quantum dot with an average particle size of 8 nm; the pore-forming agent is composed of NH4HCO3 and PMMA microspheres in a weight ratio of 2:1, and the particle size ranges from 50 μm to 200 μm; and the sintering aid is CeBO3.
[0064] S2, the temperature is raised to 700 DEG C in an argon atmosphere and kept for 3 hours, then kept for 1.5 hours at 450 DEG C in a hydrogen atmosphere, a porous structure is formed, and finally the temperature is lowered to room temperature, to obtain the metal ceramic composite material for preparing hydrogen-rich water.
[0065] Example 5 The embodiment provides a metal ceramic composite material for preparing hydrogen-rich water, and a preparation process thereof is as follows. S1, take the nano metal phase, the doped aluminum-based alloy particles, the ceramic matrix, the functional adjuvant, the pore-forming agent and the sintering aid in a weight ratio of 30:30:60:15:10:5, mix and dry-press into shape under 80 MPa; wherein the nano metal phase is the Mg-Ni / ZnO powder of Example 1, the doped aluminum-based alloy particles are the Al-Ga-In / Pt powder of Example 2; the ceramic matrix is composed of nano Al2O3, nano TiO2, ZrO2 and MgO in a molar ratio of 3:2:2:1; the functional adjuvant is carboxyl-modified graphene quantum dots with an average particle size of 8 nm; the pore-forming agent is composed of NH4HCO3 and PMMA microspheres in a weight ratio of 2:1, with a particle size range of 50 μm~200 μm; and the sintering aid is CeBO3.
[0066] S2, heat to 800℃ in an argon atmosphere and keep for 2 hours, then keep at 500℃ in a hydrogen atmosphere for 1 hour, form a porous structure, and finally cool to room temperature to obtain the metal ceramic composite material for preparing hydrogen-rich water.
[0067] Comparative Example 1 This comparative example provides a metal ceramic composite material for preparing hydrogen-rich water, the difference between its preparation process and that of Example 3 is only that magnesium powder is used instead of Mg-Ni alloy powder.
[0068] Comparative Example 2 This comparative example provides a metal ceramic composite material for preparing hydrogen-rich water, the difference between its preparation process and that of Example 3 is only that Mg-Ni alloy powder is used instead of Mg-Ni / ZnO powder.
[0069] Comparative Example 3 This comparative example provides a metal ceramic composite material for preparing hydrogen-rich water, the difference between its preparation process and that of Example 3 is only that no doped aluminum-based alloy particles are added.
[0070] Comparative Example 4 This comparative example provides a metal ceramic composite material for preparing hydrogen-rich water, the difference between its preparation process and that of Example 3 is only that no carboxyl-modified graphene quantum dots are added.
[0071] Comparative Example 5 This comparative example provides a metal ceramic composite material for preparing hydrogen-rich water, the difference between its preparation process and that of Example 3 is only that no CeBO3 is added.
[0072] The hydrogen-rich water was prepared according to the following method using the materials in Examples 3-5 and Comparative Examples 1-5, and the hydrogen concentration and service life were tested: 500 ml of drinking water was placed in a beaker, 30 g of the metal ceramic composite material was added, and after standing for 1 h, the hydrogen concentration of the water was immediately tested using a hydrogen tester, and the hydrogen concentration was read. Continue to stand, and during the standing process, test the hydrogen concentration of the water every 1 h using a hydrogen tester, and when the hydrogen concentration is lower than 500 ppb, stop testing, and determine the service life as the time of the last test.
[0073] The materials in Examples 3-5 and Comparative Examples 1-5 were made into 2 cm*2 cm*2 cm cubes, and the density of the materials was tested using a density meter to obtain the density.
[0074] The test results are shown in Table 1.
[0075] Table 1
[0076] As can be seen from the above, the hydrogen production capacity of the material of Example 3 is higher than that of the material of Comparative Example 1, and the service life is longer than that of the material of Comparative Example 1, indicating that the addition of Ni element can improve the hydrogen production rate and prolong the service life of the material. The main reason is that the addition of Ni element improves the catalytic activity of the material, and also inhibits the oxidation of magnesium and promotes the transfer of electrons, prolonging the service life of the material.
[0077] The hydrogen production capacity of the material of Example 3 is higher than that of the material of Comparative Example 2, and the service life is longer than that of the material of Comparative Example 2. In pure Mg-Ni alloy, Mg hydrolysis generates Mg(OH)2, which is a difficultly soluble substance that forms a continuous covering layer on the surface of the alloy, which is easy to crack due to volume expansion (Mg→Mg(OH)2 volume increase) and re-agglomerate, eventually completely wrapping the active metal, preventing water from contacting the internal Mg, which reduces the hydrogen production efficiency and also reduces the service life. The presence of ZnO can physically separate the Mg-Ni particles, avoiding the loss of active sites due to the covering of the Mg(OH)2 layer during the reaction; ZnO as a spacer phase can block the excessive growth and agglomeration of the Mg(OH)2 product layer, maintaining the pore structure inside the particles and providing a channel for water diffusion.
[0078] The hydrogen production capacity of the material of Example 3 is higher than that of the material of Comparative Example 3, and the service life is longer than that of the material of Comparative Example 3, indicating that the addition of doped aluminum-based alloy particles can significantly improve the hydrogen production rate and prolong the service life of the material. The main reason is that the Al-Ga-In alloy continuously destroys the passivation layer through the micro-battery effect, prolonging the service life of the material; the Pt nanocluster catalyzes water decomposition, significantly improving the hydrogen production rate.
[0079] The hydrogen production capacity of the material of Example 3 is higher than that of the material of Comparative Example 4, indicating that the addition of the surface carboxyl-modified graphene quantum dots can significantly improve the hydrogen production rate. The main reason is that the surface carboxyl-modified graphene quantum dots have hydrophilicity, which enhances the hydrophilicity of the material and can promote the dissolution efficiency of hydrogen in water, thereby increasing the saturated hydrogen concentration of the hydrogen-rich water.
[0080] The denseness of the material of Example 3 is higher than that of the material of Comparative Example 5, indicating that the addition of CeBO3 improves the denseness of the material. The main reason is that CeBO3 as a sintering aid can interact with the ceramic matrix, improve the viscosity of the liquid phase, promote sintering densification, and thus improve the denseness of the material.
[0081] The above examples are only illustrative of the principles and effects of the present application, and are not intended to limit the present application. Any person skilled in the art can modify or change the above examples without departing from the spirit and scope of the present application. Therefore, all equivalent modifications or changes made by those skilled in the art without departing from the spirit and technical ideas disclosed in the present application shall be covered by the claims of the present application.
Claims
1. A cermet composite material for producing hydrogen-rich water, characterized by comprising a metal oxide and a metalloid element. The metal ceramic composite material for preparing hydrogen-rich water has a porous structure and is prepared by sintering after raw materials are mixed and formed; The raw materials include a nano metal phase, doped aluminum-based alloy particles, a ceramic matrix, a functional additive, a pore-forming agent and a sintering aid, with a weight ratio of 10-30:10-30:30-60:5-15:5-10:2-5. The nano metal phase is magnesium-based alloy particles with a core-shell structure, which includes an inner core and an outer shell, wherein the inner core is a magnesium-nickel alloy and the outer shell is a zinc oxide coating layer. The doped aluminum-based alloy particles are aluminum-gallium-indium alloy particles with platinum nanoclusters loaded on the surface. The functional additive is hydrophilic graphene quantum dots.
2. The metal ceramic composite material for hydrogen-rich water production according to claim 1, characterized by: The thickness of the zinc oxide coating layer in the magnesium-based alloy particles with a core-shell structure is 5 nm-20 nm. And / or, the loading amount of platinum in the doped aluminum-based alloy particles is 0.1wt%-1wt%.
3. The metal ceramic composite material for hydrogen-rich water production according to claim 1, characterized by: The ceramic matrix includes nano-aluminum oxide, nano-titanium dioxide, zirconium dioxide and magnesium oxide. And / or, the pore-forming agent includes ammonium bicarbonate and polymethyl methacrylate. And / or, the sintering aid is cerium borate. And / or, the hydrophilic graphene quantum dots are graphene quantum dots with surface carboxyl modification.
4. The metal ceramic composite material for hydrogen-rich water production according to claim 3, characterized by: The ceramic matrix includes nano-aluminum oxide, nano-titanium dioxide, zirconium dioxide and magnesium oxide, with a molar ratio of 1-4:1:1-3:
1. And / or, the pore-forming agent includes ammonium bicarbonate and polymethyl methacrylate, with a weight ratio of 1-4:
1. And / or, the pore-forming agent is composed of a mixture of ammonium bicarbonate and polymethyl methacrylate microspheres, with a particle size of 50μm-200μm.
5. The metal ceramic composite material for hydrogen-rich water production according to any one of claims 1 to 4, characterized by: The specific surface area of the metal ceramic composite material for preparing hydrogen-rich water is 50 m² / g-100 m² / g.
6. The method for preparing the metal-ceramic composite material for producing hydrogen-rich water according to any one of claims 1 to 5, characterized in that, The method comprises the following steps: The nano metal phase, doped aluminum-based alloy particles, ceramic matrix, functional additive, pore-forming agent and sintering aid are mixed and formed, and then sintered to obtain the metal ceramic composite material for preparing hydrogen-rich water.
7. The method of claim 6, wherein: The mixed forming method is dry pressing or injection molding, and the dry pressing pressure is 50 MPa-100 MPa.
8. The production method according to claim 6 or 7, characterized in that: The sintering process includes: heating to 600℃-800℃ in a protective atmosphere for 2-4 hours, then heating to 400℃-500℃ in a hydrogen atmosphere for 1-2 hours to form a porous structure, and finally cooling to room temperature to obtain the metal ceramic composite material for preparing hydrogen-rich water.
9. Use of the metal ceramic composite material for preparing hydrogen-rich water according to any one of claims 1-5 and / or the metal ceramic composite material for preparing hydrogen-rich water prepared by the method according to any one of claims 6-8 in the preparation of hydrogen-rich water.
10. An apparatus for producing hydrogen-rich water, characterized by comprising: The hydrogen-rich water preparation module comprises the metal ceramic composite material for preparing hydrogen-rich water according to any one of claims 1-5 and / or the metal ceramic composite material for preparing hydrogen-rich water prepared by the method according to any one of claims 6-8.